2015
DOI: 10.1039/c5ra03512k
|View full text |Cite
|
Sign up to set email alerts
|

High concentration DNA solubility in bio-ionic liquids with long-lasting chemical and structural stability at room temperature

Abstract: DNA (Salmon testes) was solubilized in a biocompatible ionic liquid at up to 8 wt% with long term (one year) structural and chemical stability upon storage at room temperature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
29
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 32 publications
1
29
1
Order By: Relevance
“…For industrial purposes, ILs are being currently applied in DNA-based biosensors (Chen et al 2013;Sun et al 2013;Machado et al 2014), or to assist a vast variety of methods in genetic manipulations, including genomic sequencing (Kulkarni and Mukherjee 2016), cloning (Li et al 2013b), or gene delivery and transformation (Zhang et al 2009;Soni et al 2015). Moreover, replacement of standard aqueous solutions by ILs as solvents and catalysts for laboratory purposes enabled to overcome certain technological limitations associated with DNA nanotechnology (Nishimura et al 2005;Dandia et al 2013) due to enhanced DNA stability and solubility in ILs (Zhang et al 2009;Sharma et al 2015;Jumbri et al 2016;Mishra et al 2016). Among others, it has been shown that plasmid DNA demonstrates an increased resistance against enzymatic degradation in aqueous ILs based on choline dihydrogen phosphate when compared to saline buffer (Mazid et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…For industrial purposes, ILs are being currently applied in DNA-based biosensors (Chen et al 2013;Sun et al 2013;Machado et al 2014), or to assist a vast variety of methods in genetic manipulations, including genomic sequencing (Kulkarni and Mukherjee 2016), cloning (Li et al 2013b), or gene delivery and transformation (Zhang et al 2009;Soni et al 2015). Moreover, replacement of standard aqueous solutions by ILs as solvents and catalysts for laboratory purposes enabled to overcome certain technological limitations associated with DNA nanotechnology (Nishimura et al 2005;Dandia et al 2013) due to enhanced DNA stability and solubility in ILs (Zhang et al 2009;Sharma et al 2015;Jumbri et al 2016;Mishra et al 2016). Among others, it has been shown that plasmid DNA demonstrates an increased resistance against enzymatic degradation in aqueous ILs based on choline dihydrogen phosphate when compared to saline buffer (Mazid et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The electrostatic interactions between the solvent and 214 carrageenan in the hydrated DESs as well as their lower viscosity are perhaps responsible for 215 the observed higher yield of κ-carrageenan. Such interaction was found to be responsible for 216 selective agarose extraction from Gracilaria dura, an agarophyte(Sharma et al, 2015). The 217 indication of the interaction between the sulphate group of κ-carrageenan and the DESs are 218 also evident from the elemental analyses data (supporting…”
mentioning
confidence: 63%
“…78 The unique characteristics of ILs made them useful in many processes in carbohydrate 79 chemistry (Murugesan & Linhardt, 2005). ILs having the imidazolium structure, such as 1- we have reported selective precipitation of agarose from seaweed (Gracilaria dura) 88 extractives using bio-based ionic liquids (Sharma et al, 2015). It should be noted that, κ-89 carrageenan is conventionally extracted using alkali following the method reported by 90 Craigie & Leigh (1978).…”
mentioning
confidence: 98%
“…However, the stability of DNA in the DES depends on the ability of DNA to maintain its helical structure, that could change during the interaction of DNA with other molecules. Recently, Sharma et al found that hydrogen bonding and electrostatic interactions between bio-ionic liquids and DNA were found to be responsible for the long-term stability of DNA [5]. This finding enhanced the importance of studying the mode of interaction between DNA-DES to provide a stable medium for DNA.…”
mentioning
confidence: 91%